Mediating effects of physical fitness index between physical activity and executive function in Chinese adolescents: an observational study - Wu, Huipan; Wang, Jinxian; Wu, Jian; Ma, Yuanyuan; Wang, Yi; Duan, Wenqing (Frontiers in Psychology, 2025)
ObjectiveTo explore the mediating effect of physical fitness index between physical activity and executive function in Chinese adolescents, and to provide a theoretical basis for improving adolescents’ physical fitness status and executive function.MethodsA total of 5,336 adolescents aged 13–18 years were sampled from September to December 2023 in Changzhi, Taizhou, Jishou, Nanchang, Suzhou, Xianyang, and Yulin, China, respectively, using stratified whole cluster random sampling. Adolescents’ physical activity, physical fitness index and executive function were assessed using questionnaires combined with tests. Descriptive analysis was used to describe the characteristics of each test index of adolescents, Pearson’s correlation was used to analyze the relationship between physical fitness index, physical activity, and executive function, and the mediation model was used to test the mediating effect of physical fitness index between physical activity and executive function.ResultsThe length of participation in moderate-to-vigorous physical activity was 110 (63, 187) min/week in the high fitness index group and 93 (53, 168) min/week in the low fitness index group, which was statistically different when comparing the two groups (Z = −4.286, p = 0.001); The response time for cognitive flexibility was (321.11 ± 142.79) milliseconds for females and (291.12 ± 137.09) milliseconds for males, which was statistically different when comparing the two groups (t = −7.816, p = 0.001). The correlation coefficient between moderate-to-vigorous physical activity and the physical fitness index was 0.039 (p < 0.05); the correlation coefficients between the physical fitness index and the 1-back response time, the 2-back response time, and the cognitive dexterity response time were −0.124, −0.180, and −0.100, respectively (all p-values < 0.05); There was no significant correlation between physical activity and any of the subfunctions of executive function (all p-values > 0.05). The mediation effect values of the physical fitness index between moderate-to-vigorous physical activity and 1-back response time, 2-back response time, and cognitive flexibility response time were −0.0007 (95% C1 = −0.0021 ~ −0.0003), −0.0013 (95% CI = −0.0039 ~ −0.0007), and −0.0004 (95% CI = − 0.0010 ~ −0.0002).ConclusionFully mediated effects of the adolescent fitness index between moderate-to-vigorous physical activity and working memory and cognitive flexibility.